A Calanais myth and an alignment of the east stone-row with both the rising of the Pleiades and crossovers of Venus at sunrise on the summer solstices. (2nd October 2021) - Nance, David Alexander
ABSTRACT: A myth asserts that at sunrise on the summer solstice 'something' came to the Calanais Stones' central ring heralded by the cuckoo's call. This paper investigates which of the three celestial objects easily visible at sunrise, the Sun, Moon and Venus, might be referred to. The stones have no obvious orientation with the Sun and, while a 'window' of the midsummer full-moons could be seen over the stone ring, complex lunar orbits preclude any precise alignments including the lunar standstill positions. Several widespread European goddesses of fertility and sovereignty were associated with both Venus and the cuckoo, astronomically symbolised by the Pleiades in northern Europe. The east -row of the Calanais Stones is aligned with crossover events of Venus. Three crossover events occurred during the period of the east row construction suggested by radiocarbon dating. The azimuth of the rising Pleiades coincided with the Venus crossover of 1677 and 1674 BC. The 'something' was 'bright, shining, holy' in Brittonic, gwen, while Gwener is the planet Venus. The appearance of the Sun and Venus at sunrise on the summer solstice might represent a divine wedding. This is believed to be the first European prehistoric monument demonstrated to be purposely aligned with Venus.